Urgensi Pewarisan Usaha Petis Udang Tradisional sebagai Pembelajaran Pendidikan Berbasis Budaya Lokal: Kajian Etnopedagogik - Ali Manshur; I Wayan Artika; I Wayan Rasna (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
This study aims to examine the urgency of transmitting traditional shrimp paste (petis udang) enterprises as a form of local culture based education from an ethnopedagogical perspective. The research was conducted at the Bawang Merah shrimp paste enterprise in Muncar District, Banyuwangi Regency, which continues to employ traditional production methods and actively involves family members and the coastal community. A qualitative approach with a case study design was employed. Data were collected through participant observation, in-depth interviews with four groups of informants (the enterprise owner, the owner’s child, workers, and community leaders), and documentation. Data analysis followed the stages of data reduction, data display, and verification, using content analysis, discourse analysis, and interpretative analysis. The findings reveal that the shrimp paste enterprise functions as a non-formal educational space where local knowledge, life skills, and character values such as hard work, patience, responsibility, discipline, and mutual cooperation are transmitted through learning by doing. The inheritance process occurs naturally through role modeling, gradual participation, and collective work interactions, reflecting core principles of ethnopedagogy and cultural enculturation. Nevertheless, the study also identifies potential dysfunctions, particularly limited adaptation to socio-economic changes and a lack of innovation that may affect younger generations’ interest in continuing the enterprise. This research underscores that traditional shrimp paste enterprises serve not only economic purposes but also play a strategic role as local culture–based learning systems that contribute to character formation, cultural identity, and the sustainability of coastal traditions